Iberian Pig as a Model To Clarify Obscure Points in the Bioavailability and Metabolism of Ellagitannins in Humans - Espín, Juan Carlos; González-Barrio, Rocío; Cerdá, Begoña; López-Bote, Clemente; Rey, Ana I.; Tomás-Barberán, Francisco a (Journal of Agricultural and Food Chemistry, 2007)
Ellagitannin-containing foods (strawberries, walnuts, pomegranate, raspberries, oak-aged wine, etc.) have attracted attention due to their cancer chemopreventive, cardioprotective, and antioxidant effects. Ellagitannins (ETs) are not absorbed as such but are metabolized by the intestinal flora to yield urolithins (hydroxydibenzopyran-6-one derivatives). In this study, Iberian pig is used as a model to clarify human ET metabolism. Pigs were fed either cereal fodder or acorns, a rich source of ETs. Plasma, urine, bile, lumen and intestinal tissues (jejunum and colon), feces, liver, kidney, heart, brain, lung, muscle, and subcutaneous fat tissue were analyzed. The results demonstrate that acorn ETs release ellagic acid (EA) in the jejunum, then the intestinal flora metabolizes EA sequentially to yield tetrahydroxy- (urolithin D), trihydroxy- (urolithin C), dihydroxy- (urolithin A), and monohydroxy- (urolithin B) dibenzopyran-6-one metabolites, which were absorbed preferentially when their lipophilicity increased. Thirty-one ET-derived metabolites were detected, including 25 urolithin and 6 EA derivatives. Twenty-six extensively conjugated metabolites were detected in bile, glucuronides and methyl glucuronides of EA and particularly urolithin A, C, and D derivatives, confirming a very active enterohepatic circulation. Urolithins A and B as well as dimethyl-EA-glucuronide were detected in peripheral plasma. The presence of EA metabolites in bile and in urine and its absence in intestinal tissues suggested its absorption in the stomach. Urolithin A was the only metabolite detected in feces and together with its glucuronide was the most abundant metabolite in urine. No metabolites accumulated in any organ analyzed. The whole metabolism of ETs is shown for the first time, confirming previous studies in humans and explaining the long persistency of urolithin metabolites in the body mediated by an active enterohepatic circulation.
From Duplicate 2 (Iberian Pig as a Model To Clarify Obscure Points in the Bioavailability and Metabolism of Ellagitannins in Humans - Espín, Juan Carlos; González-Barrio, Rocío; Cerdá, Begoña; López-Bote, Clemente; Rey, Ana I; Tomás-Barberán, Francisco A)From Duplicate 2 (Iberian Pig as a Model To Clarify Obscure Points in the Bioavailability and Metabolism of Ellagitannins in Humans - Espín, Juan Carlos; González-Barrio, Rocío; Cerdá, Begoña; López-Bote, Clemente; Rey, Ana I; Tomás-Barberán, Francisco A)The following values have no corresponding Zotero field: publisher: American Chemical Society accession-num: 17990850
Keywords: Animal; Animals; bile; bioavailability; Biological Availability; Body Fluids; Body Fluids: chemistry; Cereals; Cereals: chemistry; colon; diet; ellagic acid; Ellagitannin; gall bladder; Humans; Hydrolyzable Tannins; Hydrolyzable Tannins: metabolism; Hydrolyzable Tannins: pharmacokinetics; intestine; metabolism; Models; Quercus; Seeds; Seeds: chemistry; Swine; Swine: metabolism; Tissue Distribution; urolithin

Iberian Pig as a Model To Clarify Obscure Points in the Bioavailability and Metabolism of Ellagitannins in Humans - Espín, Juan Carlos; González-Barrio, Rocío; Cerdá, Begoña; López-Bote, Clemente; Rey, Ana I; Tomás-Barberán, Francisco a (Journal of Agricultural and Food Chemistry, 2007)
Ellagitannin-containing foods (strawberries, walnuts, pomegranate, raspberries, oak-aged wine, etc.) have attracted attention due to their cancer chemopreventive, cardioprotective, and antioxidant effects. Ellagitannins (ETs) are not absorbed as such but are metabolized by the intestinal flora to yield urolithins (hydroxydibenzopyran-6-one derivatives). In this study, Iberian pig is used as a model to clarify human ET metabolism. Pigs were fed either cereal fodder or acorns, a rich source of ETs. Plasma, urine, bile, lumen and intestinal tissues (jejunum and colon), feces, liver, kidney, heart, brain, lung, muscle, and subcutaneous fat tissue were analyzed. The results demonstrate that acorn ETs release ellagic acid (EA) in the jejunum, then the intestinal flora metabolizes EA sequentially to yield tetrahydroxy- (urolithin D), trihydroxy- (urolithin C), dihydroxy- (urolithin A), and monohydroxy- (urolithin B) dibenzopyran-6-one metabolites, which were absorbed preferentially when their lipophilicity increased. Thirty-one ET-derived metabolites were detected, including 25 urolithin and 6 EA derivatives. Twenty-six extensively conjugated metabolites were detected in bile, glucuronides and methyl glucuronides of EA and particularly urolithin A, C, and D derivatives, confirming a very active enterohepatic circulation. Urolithins A and B as well as dimethyl-EA-glucuronide were detected in peripheral plasma. The presence of EA metabolites in bile and in urine and its absence in intestinal tissues suggested its absorption in the stomach. Urolithin A was the only metabolite detected in feces and together with its glucuronide was the most abundant metabolite in urine. No metabolites accumulated in any organ analyzed. The whole metabolism of ETs is shown for the first time, confirming previous studies in humans and explaining the long persistency of urolithin metabolites in the body mediated by an active enterohepatic circulation.
From Duplicate 2 (Iberian Pig as a Model To Clarify Obscure Points in the Bioavailability and Metabolism of Ellagitannins in Humans - Espín, Juan Carlos; González-Barrio, Rocío; Cerdá, Begoña; López-Bote, Clemente; Rey, Ana I; Tomás-Barberán, Francisco A)
Keywords: Animal; Animals; bile; bioavailability; Biological Availability; Body Fluids; Body Fluids: chemistry; Cereals; Cereals: chemistry; colon; diet; ellagic acid; Ellagitannin; gall bladder; Humans; Hydrolyzable Tannins; Hydrolyzable Tannins: metabolism; Hydrolyzable Tannins: pharmacokinetics; intestine; metabolism; Models; Quercus; Seeds; Seeds: chemistry; Swine; Swine: metabolism; Tissue Distribution; urolithin

Effect of age at the beginning of the free-range fattening period on growth and carcass and fat quality in Iberian pigs - Daza, Argimiro; López-Bote, Clemente; Rey, Ana; Olivares, Álvaro; Olivares, Álvaro (Archives of Animal Nutrition, 2006)
Abstract This experiment was carried out to study the influence of age at the beginning of the free-range fattening period (traditional pigs, TP, age 12 months vs. young pigs, YP, age 8 months) on the performance of Iberian pigs. During 152 days prior to the fattening period, TP and YP pigs received 1.7 and 2.6 kg feed per day, respectively. During fattening, TP pigs had a higher average daily gain (p < 0.05) than YP pigs. The proportions of PUFA and n-3 fatty acids of the outer and inner layers of subcutaneous backfat were higher in TP than in YP pigs (p < 0.05), while the proportions of C16:0 and SFA in the inner layer of subcutaneous backfat were greater in YP than in TP pigs (p < 0.05). The ratio of n-6/n-3 in subcutaneous backfat was lower in TP than in YP pigs (p < 0.05). The percentage of intramuscular fat in longissimus dorsi muscle was higher in TP than in YP pigs (p < 0.05). The relationship between the percentage of intramuscular fat in longissimus dorsi muscle and average daily gain during the free-range fattening period adjusted to a quadratic function (p < 0.05). The concentration of α- and ?-tocopherol in subcutaneous backfat at slaughter was significantly higher in TP than in YP pigs (p < 0.05). It is concluded that Iberian pigs that have 8 months of age at the beginning of free-range feeding have adequate commercial quality.
From Duplicate 2 (Effect of age at the beginning of the free-range fattening period on growth and carcass and fat quality in Iberian pigs - Daza, Argimiro; López-Bote, Clemente; Rey, Ana; Olivares, Álvaro)
Keywords: a and g tocopherols; Adipose Tissue; Adipose Tissue: metabolism; Age Factors; alpha-Tocopherol; alpha-Tocopherol: analysis; Animal Feed; Animal Nutritional Physiological Phenomena; Animals; Body Composition; Body Composition: physiology; carcass quality; fatty acid proﬁle; fatty acids; Fatty Acids: analysis; free-range fattening; gamma-Tocopherol; gamma-Tocopherol: analysis; Growth; Male; Muscle; Pig age; Skeletal; Skeletal: anatomy & histology; Skeletal: chemistry; Swine; Swine: growth & development; Weight Gain

Effect of age at the beginning of the free-range fattening period on growth and carcass and fat quality in Iberian pigs - Daza, Argimiro; López-Bote, Clemente; Rey, Ana; Olivares, Álvaro; Olivares, Álvaro (Archives of Animal Nutrition, 2006)
Abstract This experiment was carried out to study the influence of age at the beginning of the free-range fattening period (traditional pigs, TP, age 12 months vs. young pigs, YP, age 8 months) on the performance of Iberian pigs. During 152 days prior to the fattening period, TP and YP pigs received 1.7 and 2.6 kg feed per day, respectively. During fattening, TP pigs had a higher average daily gain (p < 0.05) than YP pigs. The proportions of PUFA and n-3 fatty acids of the outer and inner layers of subcutaneous backfat were higher in TP than in YP pigs (p < 0.05), while the proportions of C16:0 and SFA in the inner layer of subcutaneous backfat were greater in YP than in TP pigs (p < 0.05). The ratio of n-6/n-3 in subcutaneous backfat was lower in TP than in YP pigs (p < 0.05). The percentage of intramuscular fat in longissimus dorsi muscle was higher in TP than in YP pigs (p < 0.05). The relationship between the percentage of intramuscular fat in longissimus dorsi muscle and average daily gain during the free-range fattening period adjusted to a quadratic function (p < 0.05). The concentration of α- and ?-tocopherol in subcutaneous backfat at slaughter was significantly higher in TP than in YP pigs (p < 0.05). It is concluded that Iberian pigs that have 8 months of age at the beginning of free-range feeding have adequate commercial quality.
From Duplicate 2 (Effect of age at the beginning of the free-range fattening period on growth and carcass and fat quality in Iberian pigs - Daza, Argimiro; López-Bote, Clemente; Rey, Ana; Olivares, Álvaro)From Duplicate 2 (Effect of age at the beginning of the free-range fattening period on growth and carcass and fat quality in Iberian pigs - Daza, Argimiro; López-Bote, Clemente; Rey, Ana; Olivares, Álvaro)The following values have no corresponding Zotero field: publisher: Taylor & Francis accession-num: 16921928
Keywords: a and g tocopherols; Adipose Tissue; Adipose Tissue: metabolism; Age Factors; alpha-Tocopherol; alpha-Tocopherol: analysis; Animal Feed; Animal Nutritional Physiological Phenomena; Animals; Body Composition; Body Composition: physiology; carcass quality; fatty acid proﬁle; fatty acids; Fatty Acids: analysis; free-range fattening; gamma-Tocopherol; gamma-Tocopherol: analysis; Growth; Male; Muscle; Pig age; Skeletal; Skeletal: anatomy & histology; Skeletal: chemistry; Swine; Swine: growth & development; Weight Gain